Natural Spawning, Early Development, and First Successful Hatchery Production of the Vermiculated Angelfish (Chaetodontoplus mesoleucus), Exploring the Influence of Temperature and Salinity - Yu-Hsuan Sun; Yu-Ru Lin; Hung-Yen Hsieh; Pei-Jie Meng (Animals)
The marine ornamental species trade relies heavily on wild-caught specimens, including the Vermiculated angelfish (Chaetodontoplus mesoleucus). Captive breeding of this species faces challenges with limited detailed knowledge available beyond 2 days post-hatch (dph) regarding the influence of environmental factors. This study provides a detailed characterization of C. mesoleucus from early development to 381 dph. Under controlled laboratory conditions, the effect of temperature (22–37 °C) on hatching rate, deformity rate, hatching period duration, time to 50% hatch, and survival rate is investigated. Additionally, the influence of different salinities (0–38 psu) on hatching rates and larval deformity rates was also examined. The optimal incubation temperatures for high hatching rate and minimal larval deformities are found to be within 25–28 °C. A lower salinity threshold of 10 psu was established for successful hatching, and the optimal salinity range for minimizing larval deformities was 33–36 psu. These findings provide crucial baseline data and practical recommendations for optimizing hatchery protocols for C. mesoleucus, contributing to enhanced larval survival and the potential for sustainable aquaculture production, thereby reducing the pressure on wild populations.